PENGUATAN STRUKTUR MODAL SEBAGAI PEMENUHAN REGULASI DAN PENDUKUNG PENGEMBANGAN BISNIS - Tedi Setiawan; Jaja Suteja; Ellen Rusliati (JRAK, 2020)
Decision on capital structure have an important role in determinig banking performance.This study aims to find alternative strategies for Bank X in fulfilling the capital requirements and to measure its the effectivities in order to reach the capital requirements of the Bank X to be in accordance with the regulations in 2018. The results of this study are expected to provide useful information related to the importance of strengthening the capital structure of the company, especially in the banking industry in order to maintain the continuity of business and to win in the market competition. The study was conducted at Bank X was located in Bandung. The research method used was survey with qualitative research approaches. While the type of research was explorative descriptive analysis. The results of the study was found three effective strategies to meet the capital needs of Bank X in 2018, namely asset revaluation, reduction in dividend payout ratio (DPR) and the issuance of subordinated bonds. These three strategies could improve Capital Adequacy Ratio (CAR). while alternative simulations need to be carried out to determine the impact of the decision making.